2017
DOI: 10.1002/smll.201602868
|View full text |Cite
|
Sign up to set email alerts
|

Localized Synthesis of Iron Oxide Nanowires and Fabrication of High Performance Nanosensors Based on a Single Fe2O3 Nanowire

Abstract: A composed morphology of iron oxide microstructures covered with very thin nanowires (NWs) with diameter of 15-50 nm has been presented. By oxidizing metallic Fe microparticles at 255 °C for 12 and 24 h, dense iron oxide NW networks bridging prepatterned Au/Cr pads are obtained. X-ray photoelectron spectroscopy studies reveal formation of α-Fe O and Fe O on the surface and it is confirmed by detailed high-resolution transmission electron microscopy and selected area electron diffraction (SAED) investigations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 67 publications
1
75
0
Order By: Relevance
“…In the case of the ZnAl 2 O 4 /ZnO MW, the well distributed ZnAl 2 O 4 nanocrystals along the MW can be spotted easily, while the diameter of nanocrystals varies from 10 to 50 nm (see Figure a). Because the diameter is the main parameter which determines the performances of individual devices, these two devices with practically the same diameter will be used in order to compare the reported two methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of the ZnAl 2 O 4 /ZnO MW, the well distributed ZnAl 2 O 4 nanocrystals along the MW can be spotted easily, while the diameter of nanocrystals varies from 10 to 50 nm (see Figure a). Because the diameter is the main parameter which determines the performances of individual devices, these two devices with practically the same diameter will be used in order to compare the reported two methods.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the main gas sensing mechanism in the case of individual structures is the modulation of the electron depletion region, respective of the conduction channel under exposure to reducing or oxidizing gases . Therefore, the structure diameter plays a major role for the gas sensing performances . It was experimentally demonstrated that the lower the diameter, the higher the gas response which can be obtained based on individual metal oxide nanostructures .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the device fabrication, the nanowires were detached from the glass/FTO substrate using an ultrasonic equipment and spread on a SiO 2 (300 nm in thickness) coated Si wafers pre‐patterned with Cr/Au contact pads. Individual NWs were contacted on their both ends by platinum contacts using a focused ion beam/scanning electron microscopy (FIB/SEM) equipment according to the procedure described by Lupan et al More details on chip design and configuration of Au/Cr electrodes are presented in previous work . The UV and gas sensing properties were performed in a test chamber as described in previous papers .…”
Section: Methodsmentioning
confidence: 99%